PENGARUH PENGGUNAAN FLY ASH PADA KUAT TEKAN BETON GEOPOLIMER DENGAN AKTIVATOR NATRIUM HIDROKSIDA (NaOH) DAN NATRIUM SILIKAT (Na2SiO3) (Inersia: Jurnal Teknik Sipil, 2025)
The study aims to find out the impact of the use of fly ash on the compressive strength of geopolymer concrete when compared to normal concrete as well as to know the optimum strength of geopolymer concrete with specified variation of activator mixture. This study uses experimental method by mixing concrete with previous research as references. The specimens used a cylinder mold with a diameter of 10 cm and a height of 20 cm with a specimens age of 7, 14, and 28 days. The total specimens is 36 with the NaOH concentration used was 14 M. The comparative ratio of NaOH and Na2SiO3 for variation I is 1,0 : 0,5, variation II 1,0 : 1,0, variation III 1,0 : 1,5. Geopolymer concrete replaces 100% of the amount of cement in normal concrete with fly ash. Compressive strength value of geopolymer concrete for variation I : 4,883 MPa, variation II : 7,856 MPa and variation III : 10,403MPa and compressive strength value of normal concrete is, 36,943MPa. The compressive strength of geopolymer concrete when compared with compressive strength of normal concrete in this study decreased with 67,28% for 7 days, 72,22% for 14 days, and 71,84% for 28 days. The optimum compressive strength of geopolymer concrete from variation of the activator mixture specified is at variation III with compressive strength of 10,403 MPa Keywords: Geopolymer Mortar, Fly ash, Compressive Strength